Transcendental Approach in Legal Aid Concept in Indonesia: A Philosophy of Law Perspective - Muhamad Akhsanul Fadli (Universitas Negeri Semarang, 2021)
Legal aid in Indonesia, especially in terms of access to justice, legal aid provided by the state to the people still relies on positive law. The law governing legal aid in Indonesia still revolves around the number of cases and the budget absorption target given to legal aid institutions that have been verified and accredited by the state for people/groups in need. Verification and Accreditation from the state with the parameters written in the law prevent those who need legal assistance if they are not categorized as poor. The requirement of the poor to access legal aid implies that access to legal aid for everyone in conflict is far from fair. Access to legal aid is very important because the goal of law is justice. In addition, legal aid aims to provide justice for those who do not have legal knowledge, in other words, are blind to the law. Justice for all is the pulse of legal aid that cannot be separated from the right to legal aid for those in need. Legal aid can be managed by the community, legal aid institutions/institutions that should provide access to those who need legal assistance and those in dispute, both poor and rich, so that justice for all is achieved. This study discusses the transcendental dimensions of legal aid. This study uses a descriptive research method that aims to analyze legal aid from aid agencies seen from the study of legal philosophy and legal aid with a transcendental dimension.